A GIS Approach to Supporting Nightlife Impact Management: The Case of Milan - Limonta, Giorgio (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Following the increasing liberalisation of commercial activities, which have taken place in the last few decades, the power of municipal authorities to schedule retail and leisure-based businesses has been reduced in its spatial extent; it now applies only to specific ‘Protection Zones’ (Zone da sottoporre a tutela). In these areas, due to environmental, social and/or traffic sustainability reasons, the freedom of private business is limited by the need to respect the right of residents to normal liveability and mobility standards. This paper describes a research by Laboratorio URB&COM (Politecnico di Milano), aimed at supporting the City of Milan in detecting those spatial contexts whose conditions suggest the application of a specific regulation, in order to control nightlife leisure’s negative externalities. A GIS-based analysis approach has proved fundamental in defining an objective and transparent evaluation path, towards the mapping of critical areas where regulation is needed. In addition, within the proposal of policy monitoring methods, a particular approach has been suggested, based entirely on the use of Information and Communication Technology (ICT).